Comparison of salbutamol efficacy in children- via themetered-dose inhaler (MDI) with Volumatic® spacerand via the dry powder inhaler, Easyhaler®, with thenebulizer - in mild to moderate asthma exacerbation: A multicenter, randomized study - Direkwatanachai C. (2017)
Background: β 2 agonist administered via anebulizer is the standard treatment for acuteasthma exacerbation. There are somelimitations for the use of nebulization. Weconducted a study to determine the efficacy ofsalbutamol administered via the pMDI withVolumatic ® spacer and the Easyhaler ® (DPI)compared to nebulization in mild to moderateasthma exacerbations in children.Methods: A multicenter, randomized,controlled study was conducted in childrenbetween 5 and 18 years of age who presented atan emergency or outpatient department. Theywere randomized to receive either 6 puffs ofsalbutamol via the pMDI with Volumatic ® spacer, or via the Easyhaler ® , or 0.15 mg/kg ofsalbutamol nebulized via oxygen (orcompressed air). The primary outcome was theclinical response which was assessed using themodified Wood's asthma score. The secondaryoutcomes were: hospitalization, asthma revisitwithin 3 days, systemic corticosteroid useand adverse events. The clinical score, oxygensaturation, PR, RR, BP and adverse eventswere recorded at time 0 (before treatment) and 20, 40 and 60 minutes after drugadministration.Results: There were no statistically significantdifferences in the clinical response between thethree groups at the 1 st , 2 nd or 3 rd dose or for theSpO 2 or the respiratory rate while the childrenin the Easyhaler ® group had significantly lesstachycardia after the 2 nd dose. No significantadverse events were noted among the threegroups.Conclusions: Salbutamol administered via pMDIwith Volumatic ® spacer or DPI (Easyhaler ® ) areas effective as salbutamol given via a nebulizerin providing effective relief of mild to moderateseverity acute asthma exacerbation in childrenbetween 5 and 18 years of age.